Color comparison of Iranian traditional architecture into television studio sets - Farkoosh, Maliheh Bahari Poor (2013)
A national television channel should contain national contents in order to have acceptable representation of the nation through its historical and cultural backgrounds. Novel aesthetic approach to television besides modern intellect of architecture, as will be argued in this thesis, opens a way to compare television with other arts such as architecture. In this thesis, following to the argument above,Iranian national television and Iranian historical architecture have been focused as example. By concentration on Iranian historical architecture, one of the most influential Iranian architectures was specified and was suggested to Iranian national television people to consider it in their programs. Specifically in Iran, virtual media such as national television programmes should present contents that portray the representation of Iranian identity adapted from real media such as Iranian arts and architecture. These contents could appear in the topic or subject of the programmes or in design elements (e.g. forms, shapes, colours and textures) or symbols of spaces showed in the programmes. However, there are still lacks of studies on colour comparison between these two media as well as the convenient technique for studio sets designers and television producers to estimate such comparison. Therefore, the aim of this research is to conveniently estimate the colour similarity of Iranian national television studio sets with one of the most influential architecture in the Safavid period i.e. Ali-Ghapoo Palace. This study adopted a correlational research method by applying some statistical manipulations for comparison purposes. Sixty images of six studio sets from Iranian national television cooking shows and thirty images of Ali-Ghapoo Palace were collected. Numerical colour histograms of Red, Green and Blue were extracted from each image of both sets. Histograms of studio sets were then separately transformed to relative histograms by mathematical formula and this method was then applied to each chosen histogram of Ali-Ghapoo Palace. Subsequently, the resulting relative histograms of each studio sets were adapted mathematically to those of Ali-Ghapoo Palace; and finally, the resulting relative histograms of all studio sets were adapted together to those of Ali-Ghapoo Palace. The results reveal that, out of six studio sets in total, two studio sets have intertwined histograms with those of Ali-Ghapoo Palace suggesting that these studio sets have many analogous colours with Ali-Ghapoo Palace. Another one studio set has separated histograms with those of Ali-Ghapoo Palace indicating that this studio set contains many different colours in comparison to Ali-Ghapoo Palace. Finally, after adapting all six studio sets with Ali-Ghapoo Palace, the result shows that all six studio sets, despite several diversities, are generally matched with Ali-Ghapoo Palace in terms of colour comparison. These results will potentially guide Iranian studio set designers and producers in adapting appropriate sets of colours in the future television programs in order to support and strengthen Iranian traditional identity.